PENGGUNAAN PARTIKEL BEH DALAM BAHASA JAWA DI PONOROGO - Fadilllah, Arif (Hasta Wiyata, 2023)
A beh particle is a form of Javanese particle in the Mataraman dialect. Its use is often found in a variety of informal conversations, both verbal and non-verbal. The purpose of this research is to describe the shape and distribution of beh particles in the Javanese Mataraman dialect. Through this research, it can be seen the mapping of the particle distribution beh in its use in sentences. In addition, this study will also look at the types of particles that can be occupied by beh particles. This research is qualitative research. The source of data was obtained from the Whatsapp group 'Group Ponorogo Update' which contains information and about what is happening around the Ponorogo area. The data collection technique in this study is for direct elements (BUL). This research was conducted by carrying out three stages, namely data provision, data analysis, and the stage of presenting data analysis. The results of this study found that the distribution of beh particles can be at the beginning of the sentence and at the end of the sentence. The form of the particle beh at the beginning of a sentence can be followed by several categories of word classes such as pronouns, nouns, particles, interrogatives, to verbs. The distribution of the beh particle at the end of a sentence can be preceded by adverb, verb, interrogative, up to, noun word class categories. The type of particle beh can occupy several types of particles such as emphases, softeners, and complements depending on the sentence.Â